Coronary Artery Bypass Surgery in Diffuse Advanced Coronary Artery Disease: 1-Year Clinical and Angiographic Results - Dourado, Luciana Oliveira Cascaes; Bittencourt, Marcio Sommer; Pereira, Alexandre Costa; Poppi, Nilson Tavares; Dallan, Luis Alberto Oliveira; Krieger, José Eduardo; Cesar, Luiz Antonio Machado; Gowdak, Luís Henrique Wolff (The Thoracic and Cardiovascular Surgeon, 2018)
Background Proper treatment of patients with diffuse, severe coronary artery disease (CAD) is a challenge due to its complexity. Thus, data on the outcomes after coronary artery bypass graft (CABG) in this population is scarce. In this study, we aimed to determine the impact of CABG on the clinical and functional status, as well as graft patency in those individuals.Methods Patients with severe and diffuse CAD who underwent incomplete CABG due to complex anatomy or extensive distal coronary involvement were evaluated preoperatively and 1 year after surgery. Postoperative coronary angiography was performed to evaluate graft patency. Graft occlusion was defined as the complete absence of opacification of the target vessel. Stratified analysis of graft occlusion was performed by graft type and territories, defined as left anterior descending artery (LAD), the left circumflex branch, and the right coronary artery territories; the latter two, grouped, were further classified as non-LAD territory.Results A total of 57 patients were included, in whom 131 grafts were placed. There was a significant improvement in Canadian Cardiovascular Society angina symptom severity (Z = –6.1; p < 0.001) and maximum oxygen uptake (p < 0.001), with a corresponding decrease in the use of long-acting nitrates (p < 0.001). The overall graft occlusion rate was 19.1%, with no significant difference between LAD and non-LAD territories (p = 0.08). However, a significantly lower occlusion rate was noted for the internal mammary artery (IMA) grafts when compared with saphenous vein grafts (p = 0.01), though this difference was only significant in the LAD territory (p = 0.04). Overall, the use of venous graft was the only predictor occlusion at 1 year (odds ratio: 4.03; p = 0.016).Conclusion In patients with diffuse CAD, incomplete CABG surgery resulted in a significant clinical improvement, with acceptable graft occlusion rates at 1 year, particularly for IMA grafts to the LAD territory.
Keywords: coronary artery bypass graft surgery; coronary artery disease; graft occlusion